Updates on Veterinary Anatomy and Physiology - Sian Rutland, Catrin; El-Gendy, Samir A.A (Veterinary Medicine and Science, 2022)
Knowledge of veterinary anatomy and physiology is essential for veterinary students, professionals, and researchers, as well as animal owners who wish to gain greater levels of understanding. This book reflects the diverse and dynamic research being undertaken on a variety of different species worldwide. It includes four sections and twelve chapters that address a myriad of topics, ranging from animal cardiovascular and musculoskeletal systems to pathology and infections, and immunity. Chapters present recent research on animals ranging from primates to horses and cattle.